A Perioperative Approach to Increase Limb Salvage When Treating Foot Ulcers in Patients With Diabetes. (29th March 2018) - Howell, Raelina S.; Criscitelli, Theresa; Woods, Jon S.; Gillette, Brian M.; Brem, Harold; Gorenstein, Scott
ABSTRACT: Foot ulceration in patients with diabetes increases the risk of lower extremity amputation. Major amputations produce substantial adverse consequences, increase length of hospital stay, diminish quality of life, and increase mortality. In this article, we describe approaches that decrease amputations and improve the quality of life for patients with diabetes and foot ulcers. We highlight the role of the perioperative nurse, who is essential to providing optimal patient care in the perioperative period. Perioperative care of patients with diabetes involves providing optimal surveillance for a break in the skin of the foot, screening for neuropathy, following guidelines for foot ulcer infections, preparing for pathophysiology‐based debridement, using adjuvant therapies, and offloading the patient's affected foot. Nurses should understand the disease process and pathophysiology and how to use these approaches in the perioperative setting to assist in curtailing the morbidity and mortality associated with foot ulcers in patients with diabetes.